Correlation between LDH, Liver Function, Platelets and Proteinuria in Preeclampsia with Severe Features - Shifa, Rifhani Ashilla; Lubis, Muara Panusunan; Lubis, Hilma Putri; Barus, Melvin Nova Gunawanto (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Objectives: To identify the relationship between LDH, bilirubin, SGPT, SGOT, and platelets with proteinuria in preeclampsia with severe features patients. Method: This study is an observational analytical with a retrospective cross-sectional design. The samplings contain 70 patients from the medical records of patients who were diagnosed with preeclampsia with severe features at H. Adam Malik Hospital Medan from January 2020 to March 2023.Results: It was found that 74.3% of the population had semiquantitative urine protein levels ≥+2. The average levels of LDH, total bilirubin, SGPT, SGOT, and platelets were 514.64 U/L, 0.9 mg/dL, 57.77 U/L, 64.01 U/L, and 197,585/mm3, respectively. Statistical analysis showed a positive association between proteinuria and LDH (p=0.001). However, there was no meaningful association between liver and platelet function and proteinuria.Conclusion: There is a relationship between LDH and proteinuria in severe preeclampsia patients.Hubungan antara LDH, Fungsi Hati, Trombosit dengan Proteinuria pada Pasien Preeklamsia BeratAbstrakTujuan: Untuk mengidentifikasi hubungan antara LDH, bilirubin, SGPT, SGOT, dan trombosit dengan proteinuria pada pasien preeklampsia dengan gejala berat.Metode: Penelitian ini merupakan penelitian analitik observasional dengan desain potong lintang retrospektif. Sampel terdiri dari 70 pasien dari rekam medis pasien yang didiagnosis dengan preeklampsia berat di RSUP H. Adam Malik Medan pada periode Januari 2020 hingga Maret 2023.Hasil: Ditemukan bahwa 74,3% dari populasi memiliki kadar protein urin semikuantitatif ≥+2. Kadar rata-rata LDH, bilirubin total, SGPT, SGOT, dan trombosit masing-masing adalah 514,64 U/L, 0,9 mg/dL, 57,77 U/L, 64,01 U/L, dan 197.585/mm3. Analisis statistik menunjukkan hubungan positif antara proteinuria dan LDH (p=0,001). Namun, tidak ada hubungan yang bermakna antara fungsi hati dan trombosit dengan proteinuria.Kesimpulan: Terdapat hubungan antara LDH dan proteinuria pada pasien preeklampsia berat.Kata kunci: hemolisis, fungsi hati, trombosit, preeklamsia berat, proteinuria